Appendix 3.4: Questionable Authorship Claim of Bongbong Marcos on the National Youth Commission Act - Philippine Journal of Third World Studies, Kasarinlan (Kasarinlan: Philippine Journal of Third World Studies; Vol 27, No 1-2-Vol 28, No 1-2 (2012-2013): Marcos Pa Rin! The Legacy and the Curse of the Marcos Regime, 2017)
Bongbong Marcos’s campaign biography highlights that h e “spearheaded” the passage of the Philippine Youth Commission Act. He was not the first among his colleagues in the Ninth Congress (1992–1995) to file a bill creating a national youth commission. Jaime C. Lopez filed HB00015, “An Act to Establish the Philippine Commission on Youth Development and for Other Purposes” on 1 July 1992, while Marcos filed HB04660, “An Act Creating the National Youth Commission, Defining Its Powers and Functions, Providing Funds Therefor, and for Other Purposes” on 10 November 1992. Moreover, it was not his version that eventually became the Youth in Nation-Building Act (Republic Act No. 8044, enacted on 6 July 1995)—it was another bill filed by Lopez on 15 December 1993, HB11614, titled “An Act Creating and Establishing the Philippine Youth Commission, Defining its Powers, Functions and Responsibilities, Appropriating Funds therefore, and for Other Purposes.”